DETEKSI Escherichia coli DAN Angka Paling Mungkin PADA AIR SUMUR DEKAT JAMBAN DIDAERAH WONOAYU, SIDOARJO - Putri Anggraeni; Evy Ratnasari Ekawati (Faculty of Health Sciences Universitas Maarif Hasyim Latif, 2020)
Water sources are grouped into several groups which are: sea water, surface water, and groundwater. According to the science of health, each person requires drinking water as much as 2.5 to 3 liters per day including the water in food. This research is descriptive research to find out the quality of the water wells in the area Wonoayu Sidoarjo. To find out if there are any impurities bacteria Escherichiacoliin well water. To find out the numbers of the bacteria Escherichia coliand APM on a water well. The results of the sudy of APM well water near the toilet in Wonoayu, Sidoarjo water quality is not recommended bacteriologically in this area. Whereas maximum levels of Escherichiacolipermitted for drinking water according to is 0 or is free from pathogenic microorganisms that originated in feces, while 50% of water samples in the area of Wonoayu contains coliform. Coliform bacteria in great numbers along with the feces will pollute the environment with 5 positive samples results contain Escherichia coliand 5 negative samples of Escherichia coli.